Medical retina CD-ROM - Chong, N. H. Victor; Downes, Susan M.; Freeman, Gwenyth M.; Sehmi, Kulwant; Holder, Graham; Bird, Alan; Moorfields Eye Hospital (London : BMJ Books, 1999)
Contains case presentations, over 85 topics, MCQs, an image library of over 1000 pictures, an animated module of the management of age related macular degeneration, an electrophysiology teaching module, oral discussions from Professor Alan Bird.
Title from disc label
CD is available at Koleksi Media, Perpustakaan HUKM
N. H. Victor Chong, et al.
System requirements: A 486 series PC with 4Mb of RAM, double speed CD ROM drive, mouse, SVGA screen capable of displaying 640 x 480 pixels, 65,000 color display (256 color displays chosen from large palettes can also be supported). 90 Mb of hard disk space for complete installation to hard disk. Microsoft Windows version 3.1 or later.
Keywords: Retinal diseases